Diabetes mellitus in dialysis and renal transplantation. (October 2021) - Ben-David, Eyal; Hull, Richard; Banerjee, Debasish
Diabetes mellitus is the commonest cause of end-stage kidney failure worldwide and is a proven and significant risk factor for the development of cardiovascular disease. Renal impairment has a significant impact on the physiology of glucose homeostasis as it reduces tissue sensitivity to insulin and reduces insulin clearance. Renal replacement therapy itself affects glucose control: peritoneal dialysis may induce hyperglycaemia due to glucose-rich dialysate and haemodialysis often causes hypoglycaemia due to the relatively low concentration of glucose in the dialysate. Autonomic neuropathy which is common in chronic kidney disease (CKD) and diabetes increases the risk for asymptomatic hypoglycaemia. Pharmacological options for improving glycaemic control are limited due to alterations to drug metabolism. Impaired glucose tolerance and diabetes are also common in the post-kidney-transplant setting and increase the risk of graft failure and mortality. This review seeks to summarise the literature and tackle the intricacies of glycaemic management in patients with CKD who are either on maintenance haemodialysis or have received a kidney transplant. It outlines changes to glycaemic targets, monitoring of glycaemic control, the use of oral hypoglycaemic agents, the management of severe hyperglycaemia in dialysis and kidney transplantation patients.